Effects of shade and nitrogen levels on quality Bangladhonia production - Moniruzzaman, M; Islam, MS; Hossain, MM; Hossain, T; Miah, MG (Bangladesh Journal of Agricultural Research, 2010)
A field experiment was conducted to determine the optimum shade level and nitrogen fertilizer for quality Bangladhonia (Eryngium foetidum L.) production at the Bangahandhu Sheikh Mujibar Rahman Agricultural University (BSMRAU) Research Farm during December 2002 to May 2003. The treatments consisted of four shade levels (0, 25, 50, and 75% shades) and five nitrogen rates (0, 115, 138, 161, and 184 kg N/ha). Shades were artificially created by using nylon nets of different mesh sizes and colours. Fifty percent shade and application of 161 kg N/ha independently as well as in combination gave the maximum fresh yield of Bangladhonia. β-carotene and vitamin C contents in Bangladhonia leaves were maximum in full sun light (0% shade) followed by 25 and 50% shade. Application of 161 kg N/ha produced the highest amount of β-carotene and vitamin C followed by 184 kg N/ha. The lowest amount of leaf fibre (1.30%) was recorded from 75% shade closely followed by 50% shade (1.76%), whereas the maximum amount of leaf protein was found at 50% shade. Application of 184 kg N/ha gave the highest amount of leaf protein and less leaf fibre that was followed by 161 kg N/ha. The results revealed that Bangladhonia performed better in terms of fresh yield and quality under 25-50% shade condition. Key Words: Bangladhonia; shade; nitrogen; yield; quality. DOI: 10.3329/bjar.v34i2.5791 Bangladesh J. Agril. Res. 34(2): 205-213, June 2009